Seasickness susceptibility and the vestibular time constant: a prospective study - Lagami, Daniel; Gutkovich, Yoni Evgeni; Jamison, Anna; Fonar, Yuri; Tal, Dror (Experimental brain research, 2024)
Human passive motion during boat, car or airplane travel may trigger motion sickness. Seasickness is the most provoking manifestation of motion sickness. It imposes major constraints on quality of life and human performance. Based on seasickness susceptibility the population is usually categorized into susceptible (S) and non-susceptible (NS). During repeated exposure some susceptible individuals undergo habituation and obtain symptoms relief, reflecting a third group of habituating (H) individuals. Recently, accumulative evidence suggests that the vestibular time constant (Tc) is associated with motion sickness susceptibility and attenuation of symptoms. These studies demonstrated that repeated passive motion stimuli lead to temporary short-term (days) changes in Tc, whereas sea sickness habituation process lasts 3 to 6 months. Therefore, the goal of the present study was to examine the behavior of Tc during the entire span of the seasickness habituation process between the H, S and NS groups to find an objective test for seasickness severity prediction. Tc of 30 subjects was prospectively evaluated pre, 3 and 6 months post exposure to sea environment using a computerized rotatory chair system protocol. Seasickness severity was evaluated by Wiker questionnaire. Significantly shorter Tc was found in the S group compared with the NS and H groups. Further analysis revealed lower maximal Slow Phase Velocity (mSPV) and nystagmus frequency (total number of beats/second) in the S group. Our results suggest that Tc, mSPV and nystagmus frequency might serve as a prediction for seasickness severity. This study was retrospectively registered on December 7th 2022 and assigned the identifier number NCT05640258.